Creation of a Novel Preoperative Imaging Review Acronym to Aid in Revision Endoscopic Sinus Surgery. (October 2022) - Karadaghy, Omar A.; Peterson, Andrew M.; Fox, Meha; White, Jacob; Bhalla, Vidur; Beahm, David; Villwock, Jennifer; Chiu, Alexander G.
Objectives: (1) Identify anatomic contributions to chronic rhinosinusitis (CRS) necessitating revision endoscopic sinus surgery (RESS). (2) Create a clinical acronym to guide imaging review prior to RESS that addresses pertinent sites of disease and potential sites of surgical morbidity. Data Sources: Ovid MEDLINE, Embase and Medline viaEmbase.com, Web of Science Core Collection, Cochrane Central Register of Controlled Trials (CENTRAL), and Google Scholar. Review Methods: Systematic search was performed using a combination of standardized terms and keywords. Studies were included if they investigated anatomic contributions to persistent CRS requiring RESS or the relationship between anatomic landmarks and surgical morbidity. Identified studies were screened by title/abstract, followed by full-text review. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were strictly followed. Results: In total, 599 articles met screening criteria, 89 were eligible for full-text review, and 27 studies were included in the final review. The identified anatomic sites of interests are broad; the most frequently cited anatomic region was retained anterior ethmoid cells (22/27 studies), followed by posterior ethmoid cells (14/27 studies). Using the consolidated information, a clinical acronym, REVISIONS, was created: Residual uncinate, Ethmoid cells (agger, Haller, supraorbital), Vessels (anterior and posterior ethmoid), Infundibulum, Septal deviation, I (eye) compartment, Onodi cell, Natural os, and Skull base slope and integrity. Conclusions: The REVISIONS acronym was developed as a tool to distill the unique anatomic contributions of primary endoscopic sinus surgery failure into a format that can be easily incorporated in preoperative radiologic review and surgical planning to optimize outcomes and minimize complications.